Pengaruh Kecepatan Crane Kapal dan Cakupan Grab terhadap Produktivitas Bongkar Muat Curah Kering - Agus Setiono, Beni; Ghanief Fairuz Zhafier, Juan (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2022)
The purpose of this study is to test and analyze the effect of partially and simultaneously the speed of ship crane equipment and the scope of grab equipment on dry bulk loading and unloading productivity. This research is located at PT. Berlian Manyar Sejahtera, which is a loading and unloading company that provides loading and unloading of dry bulk, in this company carrying out loading and unloading activities of dry bulk using ship cranes and grabs as aids. This type of correlation research uses a questionnaire as the main tool in collecting data and information from respondents who are part of the primary data. The sample in this study is productivity data for dry bulk loading and unloading activities in 2022 using crane and grab equipment according to the responses of 52 respondents. The results of the study explained that partially and simultaneously the speed of ship cranes and grab coverage have a significant influence on dry bulk loading and unloading productivity. The research results also show that Grab coverage has a better ability than ship crane speed on dry bulk loading and unloading productivity at PT. Berlian Manyar Sejahtera.